ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LIKUIDITAS PADA BANK CAMPURAN KONVENSIONAL TAHUN 2010-2014 - CAHYO RUSLIAN, SANDY (Jurnal Akuntansi AKUNESA, 2016)
Liquidity is the ability of companies to repay short-term obligations. To assess the soundness of the banking one of which can be viewed by using the liquidity ratio. The liquidity ratio is the ratio of the amount of loans extended by banks in comparison with the amount of revenue that is generated from various sources (customers). Many factors can affect liquidity. The aim of this study was to analyze the effect of deposit growth, operational costs to operating income, inflation and liquidity in the BI Rate to mix conventional bank in 2010-2014. The population in this study is a company belonging to a mix of conventional banks the period 2010-2014. Data used is secondary data in the form of financial statements obtained from Bank Indonesia period 2010-2014. The sampling technique in this study using purposive sampling, the sampling using the criteria in order to get 9 companies in this study. In this study using four independent variables which include growth in deposits, operational costs to operating income, inflation and BI Rate. As for the dependent variable is the liquidity (LDR). This study was analyzed using multiple linear regression analysis. The results showed that simultaneously all variables has no effect on liquidity . In this study 2.2% of liquidity is influenced by variables TPF growth , ROA, inflation and BI Rate. While 97.8 % is influenced by other variables outside the model .